A critique of definitions in economics from an Austrian perspective: macroeconomics. Issue 1 (16th May 2016) - Davidson, Laura; Block, Walter E
Abstract : Purpose: – The purpose of this paper is to clarify definitions in economics. Design/methodology/approach: – To apply the insights of Austrian economics to terms widely used in the profession. Findings: – The authors find that the Austrian approach brings clarification to communication. Originality/value: – The authors know of no other such attempt. Therefore this paper presumably has some originality.